The Role of the Ministry of Religious Affairs in Facing the Challenges of Islamic Education in the Digital Age - Roidah Lina; Qiyadah Robbaniyah; Diningrum Citraningsih; Ika Sari (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
This study aims to determine the role of the Ministry of Religious Affairs in facing educational challenges in the digital era. Data was collected in DIY in 5 districts—descriptive qualitative research method with data collection of interviews, observations, and documentation. The result of this research is that the Ministry of Religious Affairs of the DIY region oversees Islamic educational institutions, both formal and non-formal. Each region's Ministry of Religious Affairs has a general and special program that accommodates the needs of each area—the development of the era in the era of digitalization. The Ministry of Religious Affairs develops educational applications to facilitate Islamic educational institutions' control, supervision, and evaluation. The applications used include E-management, electronic madrasah activity plan, and budget (ERKAM), madrasah digital report card (RDM), Geschool application, E-learning, electronic learning, Jogja Digital Madrasah